Implementation of the compulsory universal testing scheme in Hong Kong: Mathematical simulations of a household-based pooling approach - Ng, Kei Shing; Hon, Jeffrey Man Hin; Chong, Stephen Chau Chun; Cheung, Howard Ho Kan; Chan, Jeffrey; Lam, Simon Ching; Hon, Benny Yiu Chung (Frontiers in Public Health, 2022)
This study aims to propose a pooling approach to simulate the compulsory universal RT-PCR test in Hong Kong and explore the feasibility of implementing the pooling method on a household basis. The mathematical model is initially verified, and then the simulation is performed under different prevalence rates and pooled sizes. The simulated population is based in Hong Kong. The simulation included 10,000,000 swab samples, with a representative distribution of populations in Hong Kong. The samples were grouped into a batch size of 20. If the entire batch is positive, then the group is further divided into an identical group size of 10 for re-testing. Different combinations of mini-group sizes were also investigated. The proposed pooling method was extended to a household basis. A representative from each household is required to perform the RT-PCR test. Results of the simulation replications indicate a significant reduction (p<0.001) of 83.62%, 64.18%, and 48.46% in the testing volume for prevalence rate 1%, 3%, and 5%, respectively. Combined with the household-based pooling approach, the total number of RT-PCR is 437,304, 956,133, and 1,375,795 for prevalence rates 1%, 3%, and 5%, respectively. The household-based pooling strategy showed efficiency when the prevalence rates in the population were low. This pooling strategy can rapidly screen people in high-risk groups for COVID-19 infections and quarantine those who test positive, even when time and resources for testing are limited.